1999
DOI: 10.1046/j.1439-0396.1999.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on nutrient digestibilities (pre‐caecal and total) in pancreatic duct‐ligated pigs and the effects of enzyme substitution

Abstract: Introduction  Exocrine pancreatic insufficiency causes digestive disturbances in humans and animals. However, although clinical symptoms of pancreatic insufficiency, e.g. steatorrhoea, only occurs after loss of 80–90% normal pancreatic secretory capacity (D iM agno et al. 1973), pancreatic enzyme supplementation does not always result in normalization of digestion (especially of fat), even with high doses of enzymes (L& ouml; ser and F& ouml; lsch 1995). In order to better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…It is likely that intestinal peptidases are not capable of digesting enough proteins to meet metabolic needs of children (e.g., pancreatic insufficiency owing to cystic fibrosis), and probably not adults (e.g., alcoholic chronic pancreatitis). Indeed, in a minipig model of complete pancreatic exocrine insufficiency it was shown that when animals were fed meals containing approximately 80 g protein per day, approximately 70% protein remains unabsorbed in the small intestine, whereas only 20% is unabsorbed in the small intestine in control animals [4,5]. Surprisingly, residual protein in feces dropped to only 40% in pancreatic insufficiency and 10% in control pigs, suggesting a possible role for hindgut digestion or fermentation in pigs.…”
Section: Protein Digestion and Human Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that intestinal peptidases are not capable of digesting enough proteins to meet metabolic needs of children (e.g., pancreatic insufficiency owing to cystic fibrosis), and probably not adults (e.g., alcoholic chronic pancreatitis). Indeed, in a minipig model of complete pancreatic exocrine insufficiency it was shown that when animals were fed meals containing approximately 80 g protein per day, approximately 70% protein remains unabsorbed in the small intestine, whereas only 20% is unabsorbed in the small intestine in control animals [4,5]. Surprisingly, residual protein in feces dropped to only 40% in pancreatic insufficiency and 10% in control pigs, suggesting a possible role for hindgut digestion or fermentation in pigs.…”
Section: Protein Digestion and Human Proteasesmentioning
confidence: 99%
“…Available studies on animals confirm that preduodenal lipases, gastric or lingual, contribute to dietary fat digestion [101][102][103][104]. No animal model of gastric lipase deficiency exists.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The pancreatic duct ligated (PL) (mini)pig is an established model for studying EPI in humans [25][26][27][28], and it also is used for in vivo testing of the efficacy of pancreatic enzymes [26,29,30]. Ligation of the ductus pancreaticus accessorius results in a complete loss of exocrine pancreatic function without affecting endocrine function [31,32].…”
Section: The Pancreatic Duct Ligated Pig As a Model For Epi In Humansmentioning
confidence: 99%
“…As exocrine pancreatic function is essential for digestion and absorption of nutrients the complete loss of pancreatic secretion causes maldigestion and malabsorption of various macro- and micronutrients [24,25,26,27]. The juvenile PL pig was used in several studies to test the effects of PEI on growth and different parameters in juveniles [23,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%